2016
DOI: 10.1177/1461444815616221
|View full text |Cite
|
Sign up to set email alerts
|

Social media and citizen engagement: A meta-analytic review

Abstract: This meta-analytic study reviews empirical research published from 2007 to 2013 with an aim of providing robust conclusions about the relationship between social media use and citizen engagement. It includes 22 studies that used self-reported measures of social media use and participation, with a total of 116 relationships/effects. The results suggest that social media use generally has a positive relationship with engagement and its three sub-categories, that is, social capital, civic engagement, and politica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
228
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(255 citation statements)
references
References 70 publications
11
228
0
16
Order By: Relevance
“…Social media use has been linked to greater civic participation (Skoric et al 2015;Zhang et al 2010). The impacts of the Facebook group remain unknown for the short term.…”
Section: Attracting and Retaining Participantsmentioning
confidence: 99%
“…Social media use has been linked to greater civic participation (Skoric et al 2015;Zhang et al 2010). The impacts of the Facebook group remain unknown for the short term.…”
Section: Attracting and Retaining Participantsmentioning
confidence: 99%
“…Much of the past decade's research on social media has shown a positive relationship between offline and online political participation (Boulianne, ; Skoric, Zhu, Goh, & Pang, ). Although numerous theories have been advanced to explain this positive association, most credit the capacity of social network sites (SNS) to foster ties between users and make available mobilizing information, either through news sharing or discussion.…”
mentioning
confidence: 99%
“…Such understandings include the awareness that although mobile social networks have been shown to facilitate, community engagement (Skoric et al, 2016) they are nevertheless political actants that evoke political results which can include inequality and need to be designed thoughtfully. Drawing upon a long-term study of young NEETs (not in education, employment or training) in Leeds for example, Thornham and Gómez Cruz found that mobile usage was more likely to be a frustrating and disempowering experience for this particular group simply because of their daily status as NEET (for example when there was no free wi-fi on hand, or when their mobile based job search efforts were rejected by the unemployment office):…”
Section: Resultsmentioning
confidence: 99%